Respuesta :
Answer:
i) [tex] 3y^2 -4y +1=0[/tex]
We can divide both sides of the equation by 3 and we got:
[tex] y^2 -\frac{4}{3}y +\frac{1}{3}=0[/tex]
Now we can complete the square and we got:
[tex] (y^2 -\frac{4}{3}y +\frac{4}{9}) +(\frac{1}{3} -\frac{4}{9})=0[/tex]
[tex] (y- \frac{2}{3})^2 =\frac{1}{9}[/tex]
We take square root on both sides and we got:
[tex] y-\frac{2}{3}= \pm \frac{1}{3}[/tex]
And the solutions for y are:
[tex] y_1 = \frac{1}{3} +\frac{2}{3}=1[/tex]
[tex] y_1 = -\frac{1}{3} +\frac{2}{3}=\frac{1}{3}[/tex]
ii) [tex] y =\frac{-b \pm \sqrt{b^2 -4ac}}{2a}[/tex]
And with [tex] a = 3, b=-4 and c =1[/tex] we got:
[tex] y =\frac{4 \pm \sqrt{(-4)^2 -4(3)(1)}}{2*3}[/tex]
And we got:
[tex] y_1 = 1 , y_2 =\frac{1}{3}[/tex]
Step-by-step explanation:
Part i
For this case we have the following function given:
[tex] 3y^2 -4y +1=0[/tex]
We can divide both sides of the equation by 3 and we got:
[tex] y^2 -\frac{4}{3}y +\frac{1}{3}=0[/tex]
Now we can complete the square and we got:
[tex] (y^2 -\frac{4}{3}y +\frac{4}{9}) +(\frac{1}{3} -\frac{4}{9})=0[/tex]
[tex] (y- \frac{2}{3})^2 =\frac{1}{9}[/tex]
We take square root on both sides and we got:
[tex] y-\frac{2}{3}= \pm \frac{1}{3}[/tex]
And the solutions for y are:
[tex] y_1 = \frac{1}{3} +\frac{2}{3}=1[/tex]
[tex] y_1 = -\frac{1}{3} +\frac{2}{3}=\frac{1}{3}[/tex]
Part ii
We can use the quadratic formula:
[tex] y =\frac{-b \pm \sqrt{b^2 -4ac}}{2a}[/tex]
And with [tex] a = 3, b=-4 and c =1[/tex] we got:
[tex] y =\frac{4 \pm \sqrt{(-4)^2 -4(3)(1)}}{2*3}[/tex]
And we got:
[tex] y_1 = 1 , y_2 =\frac{1}{3}[/tex]